Pengaruh Motivasi Kerja Pegawai, Disiplin Kerja, Terhadap Kinerja Pegawai Pada Dinas Peternakan Dan Kesehatan Hewan Provinsi Sulawesi Selatan - Bunna, Trisno Heandrik; Natsir, Muhammad; Syam, Andi Hendra; Bulo, Yenni Pratiwi (STIM-LPI Makassar, 2025)
This research aims to analyze: 1) To determine the influence of work motivation on employee performance at the Livestock and Animal Health Service of South Sulawesi Province. 2) To determine the effect of work motivation on employee work discipline at the Livestock and Animal Health Service of South Sulawesi Province. 3) To determine the effect of work discipline on employee performance at the South Sulawesi Province Animal Husbandry and Animal Health Service. 4) To find out the variables that most dominantly influence employee performance at the South Sulawesi Province Animal Husbandry and Animal Health Service. The population is 133 people. The sampling technique used is a saturated sample, the entire population is sampled. The analysis technique used is multiple linear regression. The research results show that the work motivation variable has a positive and significant effect on employee performance, the work motivation variable has a positive and significant effect on employee performance, and work discipline has a positive and insignificant effect on employee performance due to problems that often disturb employees at the South Sulawesi Province Animal Husbandry and Animal Health Service .